Hubungan Membaca Berita Online di Line Today dengan Kepuasan Membaca Audience - Irham Fauzan; Maman Suherman (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. Line is one of the biggest social media in Indonesia, and one of its favorite features is Line Today. This research departs from the uses and gratification theory, and conceptually discusses the frequency, duration, content of news messages. The variables in this study are reading online news and the variable of audience satisfaction. The research method used in this research is quantitative research and correlational quantitative approach. The results found in this study are, the relationship between the frequency of reading news on Line Today with audience reading satisfaction, the relationship between the two variables has a strong positive relationship. The relationship between the duration of reading online news on Line Today with audience reading satisfaction, the relationship between these two variables has a strong positive relationship. The relationship between the content of the online news message Line Today with audience reading satisfaction, the relationship between the two variables has a strong positive relationship. The relationship between reading online news on Line Today with audience reading satisfaction, the relationship between these two variables has a strong positive relationship. Abstrak. Line adalah salah satu media sosial terbesar di Indonesia, dan salah satu fitur favoritnya adalah Line Today. Penelitian ini berangkat dari teori uses and gratification, dan secara konseptual membahas tentang frekuensi, durasi, isi pesan berita. Variabel dalam penelitian ini adalah membaca berita online dan variabel kepuasan penonton. Metode penelitian yang digunakan dalam penelitian ini adalah penelitian kuantitatif dan pendekatan kuantitatif korelasional. Hasil yang ditemukan dalam penelitian ini adalah, hubungan antara frekuensi membaca berita di Line Today dengan kepuasan membaca khalayak, hubungan antara kedua variabel tersebut memiliki hubungan positif yang kuat. Hubungan antara durasi membaca berita online di Line Today dengan kepuasan membaca khalayak, hubungan antara kedua variabel tersebut memiliki hubungan positif yang kuat. Hubungan antara isi pesan berita online Line Today dengan kepuasan membaca khalayak, hubungan kedua variabel memiliki hubungan positif yang kuat. Hubungan antara membaca berita online di Line Today dengan kepuasan membaca khalayak, hubungan antara kedua variabel tersebut memiliki hubungan positif yang kuat.